2011
DOI: 10.1016/j.immuni.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Virus Infection Enforces Demethylation of the Locus that Encodes PD-1 in Antigen-Specific CD8+ T Cells

Abstract: SUMMARY Functionally exhausted T cells express high levels of the PD-1 inhibitory receptor, and therapies that block PD-1 signaling show promise for resolving chronic viral infections and cancer. Using human and murine systems of acute and chronic viral infections we analyzed epigenetic regulation of PD-1 expression during CD8 T cell differentiation. During acute infection, naïve to effector CD8 T cell differentiation was accompanied by a transient loss of DNA methylation of the Pdcd1 locus that was directly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
359
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(390 citation statements)
references
References 87 publications
22
359
1
2
Order By: Relevance
“…Interestingly, among differentially methylated genes was also HNRNPLL, involved in alternative splicing of CD45 to the Tmem signature isoform CD45RO, and the two homing-related receptors, SELL (L-selectin) and CCR7, suggesting that the permanent change in the recirculation pattern with transition from Tcm to Tem is epigenetically fixed. For others, concordant epigenetic changes have already been described in murine CD8 + T cells (e.g., BATF, LEF1, PDCD1, TBX21, TCF7, ZBTB32;Scharer et al, 2013;Youngblood et al, 2011;Hashimoto et al, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, among differentially methylated genes was also HNRNPLL, involved in alternative splicing of CD45 to the Tmem signature isoform CD45RO, and the two homing-related receptors, SELL (L-selectin) and CCR7, suggesting that the permanent change in the recirculation pattern with transition from Tcm to Tem is epigenetically fixed. For others, concordant epigenetic changes have already been described in murine CD8 + T cells (e.g., BATF, LEF1, PDCD1, TBX21, TCF7, ZBTB32;Scharer et al, 2013;Youngblood et al, 2011;Hashimoto et al, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…We know that PD‐1 expression in CD8 + T cells results from chronic antigenic exposure in the tumour tissue [37]. However, recent evidence describes that in the case of chronic infection, permanent PD‐1 expression in T RM cells is imprinted epigenetically and is antigen‐independent [38, 39]. Additionally, PD‐1 signalling has been demonstrated to be important for antigen‐independent maintenance of memory CD8 + T cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…This stability of the exhausted phenotype is supported by epigenetic studies showing that chronic LCMV clone-13 infections induce profound and permanent de-methylations in the PD-1 promoter region. The de-methylation was maintained in antigen-specific T-cells long after LCMV clone-13 virus load has dropped below detectable levels in the blood 65 . A lack of methylation in the PD-1 promoter region has also been observed among antigen-specific CD8 T-cells from HIV patients which have been treated long-term (>2 years) with anti-retroviral therapy or in elite controllers 66 What remains unknown, however, is when T-cells undergo this differentiation.…”
Section: T-cells Undergo Stable Differentiation In Persisting Infectimentioning
confidence: 98%
“…So far, the reduced ability of T-cells to produce cytokines in chronic infections has been seen as a sign of deteriorating T-cell function but this phenotype could also simply represent an effector stage that is optimized to cause less inflammation and immunopathology than normal effector T-cells. Such an adjustment in combination with persisting expression of PD-1 could be of vital importance in chronic infections 64,65 . In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 99%